Synthesis and Luminescence Properties of (Y, Gd) (P, V)O4:Eu3+, Bi3+Red Nano-phosphors with Enhanced Photoluminescence by Bi3+, Gd3+ Doping - Pu, Yong; Tang, Ke; Zhu, Da-Chuan; Han, Tao; Zhao, Cong; Peng, Ling-Ling (Nano-Micro Letters, 2013)
A series of (Y1−y, Gd y )0.95−x(P y , V1−y)O4:0.05Eu3+, xBi3+ phosphors have been successfully prepared by a subsection method. The crystal structure, surface morphology and luminescence properties were investigated. It was found that the sintered samples crystallized in a tetragonal crystal system with space group I41/amd(a = b = 0.7119 nm, c = 0.6290 nm). The products presented rod-like morphology with length of 100–150 nm and width of 50–100 nm. A maximum peak at 619 nm (5D0 →7F2) was observed in emission spectrum of the phosphors. It was also found that co-doping of Bi3+, P5+ and Gd3+ions into YVO4:Eu3+ can not only made the right edge of the excitation band shift to the long-wavelength region, but also increased the emission intensity at 619 nm sharply and decreased the lifetime of fluorescence decay. These results may expand the application scope of the phosphors.